Understanding online gaming habits and attitudes among youth: a FGD study of gaming behaviours, social interactions, and psychological effects - Loh, Yoke Ling; Muhamad S. Ibrahim; Ahmad Sauffiyan Hasan; Josry Sakian (Penerbit Universiti Kebangsaan Malaysia, 2024)
Asia has one of the highest incidences of online gaming, making it a favourite pastime among youth worldwide. However, research shows that excessive gaming can have detrimental effects on one's health, academic performance, and social development, and the economic relevance of the online gaming industry emphasizes the need to understand the attitudes and behaviours of youth towards online gaming. Therefore, this study aimed to explore the attitudes and habits of youth towards online gaming to develop strategies that promote healthy gaming behaviour. The study used a focus group discussion with three groups of youth, totalling 16 participants. The study found that the participants engaged in prolonged online gaming sessions, and individuals had different motivations for playing games, including relaxation, stress relief, escapism, and achievement. The findings demonstrated the varied ways in which gaming can impact socialization and psychological, both positively and negatively. While gaming can provide relaxation and social connection, it can also lead to negative impacts, such as distraction and addiction. Additionally, the data from the participants in this study reveal a range of potential psychological issues associated with online gaming, including anger management, the conflict between parents and children, addiction, risky behaviours, and compulsive behaviour. The findings of this study can help Malaysian politicians, educators, and parents create measures to encourage healthy gaming behaviours and lessen the harmful effects of excessive gaming.